Preparação e caracterização de filmes fotoluminescentes de blenda polifluoreno/borracha nitrílixa (PF/NBR) - Barbosa, Camila Gouveia [UNIFESP] (2013)
With the objective of obtaining homogeneous and stable films of polyfluorene, with low excimer formation in the solid state, the copolymer poly[(9,9-dioctylfluorene)-co-phenylene] (PF) was synthesized via the Suzuki reaction and incorporated in an elastomeric matrix (nitrile rubber – NBR); films of the polymeric blend were prepared based on the proportions of 1, 5, 10, 20 and 50 % (m/m) of PF in NBR. The films were prepared using casting, spin coating and Langmuir-Blodgett. The results of the characterization techniques performed in this study indicate that it was possible to obtain a more stable material, without changes in the luminescent properties of PF, with lower excimer formation in the solid state and with an increase of the effective conjugation of the polymer. Besides that, the nitrile rubber was fundamental for the preparation of homogeneous films, using the three methodologies presented.